The Effect of The ROPES Learning Model with the Assistance of Crocodile Physics on Students’ Critical Thinking Skills in Mechanical Waves Material - Karlina Muzianti, Intan; Aripin, Aripin; Sofi Makiyah, Yanti (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
Based on the results of a preliminary study at SMA Negeri 2 Garut it is known that students' activeness is still lacking and students' critical thinking skills are classified as low. In addition, limited laboratory space makes learning less than optimal because it rarely does practicum. One effort that can be done to overcome this problem is to apply the ROPES learning model. Laboratory space limitations can be overcome by practicing crocodile physics. The purpose of this study was to determine the effect of the ROPES learning model assisted by crocodile physics on students' critical thinking skills in mechanical wave material in class XI MIPA SMA Negeri 2 Garut in the 2022/2023 academic year. This study used a quasi-experimental method with a nonequivalent control group research design. Instrument of students' critical thinking skills is carried out by giving tests in the form of essays with each question consisting of one indicator of critical thinking. The results of t-test at the significance level (α=0,05) show that tcount>ttable which means H0 is rejected, so it can be concluded that the ROPES learning model assisted by crocodile physics has a significant effect on critical thinking skills in mechanical wave material.